EFEKTIVITAS WHISTLEBLOWING DALAM MENCEGAH FRAUD: MEWUJUDKAN TRANSPARANSI DAN INTEGRITAS DI LINGKUNGAN KORPORASI - Mara, Alfida Nesa; Apandi, Sekar Ayu; Handini, Shahnaz Azka; Habibah, Siti; Farida, Ida (CV. Denasya Smart Publisher, 2025)
Whistleblowing according to Park et al. (2008) is reporting improper actions to individuals or organizations believed to have the power to stop it. Singleton (2010) defines fraud as the behavior of obtaining beneficial benefits intentionally by abusing work / position or taking assets / resources in the company. In the context of its implementation, whistleblowing is still questionable regarding its effectiveness in preventing fraud in the corporate environment, especially to create transparency and integrity. This study uses a qualitative method that focuses on reviewing the natural setting of a phenomenon that has occurred and produces a narrative description. The review shows that the lack of effectiveness of whistleblowing can be influenced by several factors, such as the lack of company socialization to employees; the absence of employee trust in the system; or the lack of whistleblower protection.